From ketogenic metabolism to targeted therapeutics: current advances in β-hydroxybutyrylation - Hu, Fangshuai; Liang, Changming; Zhang, Xu; Xu, Lishuai; Wu, Chengwei; Wan, Senlin; Wang, Jiawei; Wang, Mengyun; Zhang, Dawei; Liu, Yongchun; Li, Zhenyuan; Wang, Xiaoming; et al. (Frontiers in Immunology, 2026)
β-Hydroxybutyrylation (Kbhb) is a novel posttranslational modification (PTM) mediated by β-hydroxybutyrate (BHB). BHB, the core product of ketogenic metabolism, serves as its direct precursor and substrate. As a hub connecting energy metabolism and the epigenetic network, Kbhb exerts bidirectional regulatory effects on abnormal tumour metabolism, cardiovascular and cerebrovascular diseases, immune regulation, and other processes. Furthermore, Kbhb is not limited to histones; it is also widely present in nonhistones and influences various biological processes, such as protein stability, metabolic and energy homeostasis regulation, pathogen virulence regulation, transcriptional regulation, and signal transduction. This review summarizes the research progress in the field of Kbhb, including the inducers of Kbhb (ketogenic diet), prediction methods for modification sites (KbhbXG, pFunK, SLAM, iBhb-Lys), regulatory elements of modification (regulatory enzymes such as ENL and SIRT6, and protein substrates), mechanisms of action in cancer (e.g., mTOR signalling pathway, cGAS-STING signalling pathway), mechanisms of action in immune-related signalling pathways and immune-active components regulation, research progress on histone and nonhistone Kbhb (e.g., Bcl6, P53, STAT1, UvSlt2), and novel therapeutic strategies for diseases based on Kbhb modification (metabolic regulation and targeted therapy), providing new insights for targeted therapy for cancer and other diseases.